An unstructured Monte Carlo ray-tracing method for solving radiative heat transfer in 3D gray semitransparent medium. (March 2019) - Fan, Chao; Li, Xiao-Lei; Xia, Xin-Lin; Sun, Chuang
Highlights: Monte Carlo ray-tracing method was applied to solve Radiative Transfer in semitransparent media discretized by 3D unstructured grids. Ray tracing process was performed based on the Beer's law. The Monte Carlo simulation and iterative solution of temperature field were decoupled. Ray tracing process was accelerated by parallel processing. Abstract: Monte Carlo ray-tracing method (MCRTM) is widely used for solving the Radiative Transfer equation (RTE) due to its high accuracy and flexibility. In this paper, a MCRTM is developed for solving the radiative heat transfer in gray semitransparent media with complex geometries which are discretized by 3D unstructured grids. A novel algorithm associated to unstructured four-node tetrahedron element is proposed for generating random emitting positions of rays, and the ray tracing process is performed based on Beer's law. Meanwhile, radiation distribution factors are used for calculating radiative source terms which are loaded to the grid. The present method is first validated by comparing the predictive results with those from previous studies on a cubic enclosure, a 3D L -shaped enclosure, and a 3D elliptical enclosure, respectively. Furthermore, a radiation-conduction heat transfer problem is examined in a cylindrical enclosure. All the comparisons show that the present method is in good agreement with these previous cases. This method can be well adapted to various complex geometries. In addition, since the source term is calculated by the radiation distribution factor, which can be reused for different conditions as long as the volumetric radiative properties remain unchanged, this will bring great advantage when coupled with other heat transfer models such as conduction, convection, combustion, etc.